Study of thyroid dysfunction in metabolic syndrome in patients of Amalapuram, Andhra Pradesh, India - Vara, Ranjith; Raj, Arugolanu Prudhvi; Maske, Pravin Gulab Rao (International Journal of Advances in Medicine, 2020)
Background: Both metabolic syndrome and thyroid dysfunction are associated with increased risk of atherosclerotic heart disease. The present study was conducted to study the Association of thyroid dysfunction and Metabolic syndrome and to find out the type of thyroid dysfunction in metabolic syndrome patients. Methods: Sixty cases were defined according to the IDF Criteria. Detailed history and necessary investigations like fasting blood sample was analyzed for total triiodothyronine (T3), total thyroxine (T4), thyroid-stimulating hormone (TSH), lipid profile, and blood glucose were undertaken. Results: In this study population of metabolic syndrome cases, the thyroid dysfunction is present in 16.7% patients. Among the thyroid dysfunction, sub clinical hypothyroidism is highly prevalent - 11.7%, The hypothyroidism is 3.3% prevalent in metabolic syndrome patients (one patient had TSH levels of more than 150 mU/L) and sub clinical hyperthyroidism is 1.7% prevalent. There were no overt hyperthyroidism patients in the study. Conclusions: This study clearly shows that, one sixth of metabolic syndrome patients or every sixth metabolic syndrome had hypothyroidism either overt or subclinical. This finding indicates a need for investigating the presence of Thyroid dysfunction during managing metabolic syndrome patients